Impact of UiTM Sarawak's community engagement program on rural secondary school students' higher education aspirations - Jumaat, Hadi; Hassan, Muhamad Hafiz; Jasni, Mohd. Dzuliqyan; Abd Aziz, Ahmad Shahir; Sahari, Mohd Khairolazlin (Universiti Teknologi MARA, Kedah, 2024)
In this paper, the author seeks to analyze the outcome of the community engagement program known as “LAI QU UiTM” held by Universiti Teknologi MARA (UiTM) Sarawak at SMK Senibong, a rural secondary school. Its objectives were concerned with raising students’ consciousness on the available higher education options and their desire to attend tertiary institutions. The study thus adopted a survey and observational research design was conducted to collect feedback from 62 students participating in the study using questionnaires. Consequently, findings reveal the level of appreciation for higher learning among students and a positive focus towards university education. Implications derived from the study call for the use of outreach programs for a targeted attempt at closing the information divide amongst the rural student populace in support of the government’s education delivery policy.